Intraoperative Endoscopy as a Navigational Adjunct in Laparoscopic Heller Myotomy for Achalasia: A Consecutive Case Series - Jonathan Alvin Nugraha Halim; Ahmad Fathi Fuadi; Dimas Erlangga Nugrahadi; Agung Aji Prasetyo (HM Publisher, 2026)
Background: Laparoscopic Heller myotomy (LHM) is a primary surgical treatment for esophageal achalasia. Achieving a complete myotomy while avoiding mucosal perforation is paramount for success, yet intraoperative challenges persist. Intraoperative endoscopy (IOE) is recommended by guidelines but remains underutilized. This study aims to illustrate the methodological application and clinical utility of a standardized IOE protocol in LHM. Methods: This study was a retrospective analysis of a prospectively maintained database of a consecutive series of patients who underwent LHM with routine IOE for achalasia at our institution in 2023. We present three consecutive cases. Preoperative evaluation included esophagography, upper endoscopy, and high-resolution manometry (HRM). The primary outcomes were the adequacy of myotomy, incidence of mucosal perforation, and postoperative symptomatic relief measured by the Eckardt score at three months. Results: Three female patients (aged 19, 30, and 65) with achalasia (Type I and II) underwent LHM with IOE. The mean preoperative Eckardt score was 9.3 ± 1.5. IOE was successfully used in all cases to: (1) precisely identify the gastroesophageal junction (GEJ) via transillumination, (2) facilitate submucosal dissection through controlled insufflation, (3) confirm mucosal integrity with an air leak test, and (4) verify a patulous GEJ post-myotomy. No mucosal perforations occurred. At three-month follow-up, the mean Eckardt score significantly improved to 0.3 ± 0.6 (p < 0.05). All patients reported resolution of dysphagia and significant improvement in nutritional status. Conclusion: Our experience with this consecutive series supports the utility of systematic IOE during LHM. It appears to be a valuable tool for enhancing procedural safety, ensuring myotomy adequacy, and achieving optimal short-term functional outcomes. These findings reinforce existing guidelines and should encourage wider adoption of this critical surgical adjunct.